(untitled) (Revista Brasileira Multidisciplinar, 2025)
Quick and accurate verification of the vigor and viability of batches of seeds are important factors for decision-making regarding the disposal of batches unsuitable for commercialization and storage costs. Also, it is necessary to discriminate between lots that have similar germination potential, and therefore, the use of rapid vigor tests is sought. Thus, the objective of this study was to determine the viability of lots of buckwheat seeds with the aid of the exudate pH test methodology. The design used was completely randomized, with a 7 x 2 x 3 factorial (lots of seeds and temperatures and imbibition periods), with four replications of 50 seeds. In seed lots from the 201/2019 harvests, the temperatures were 25º and 30º C and the soaking periods were 20, 40 and 60 minutes. It was found that there was a response to imbibition and different temperatures, however with low batch stratification sensitivity. It was concluded that the exudate pH test with the presence of the seed coat was not efficient in discriminating batches of buckwheat seeds and is not suitable for this crop.